Neurogenesis in the adult brain functionally contributes to the maintenance of chronic neuropathic pain - Tan, Linette Liqi; Alfonso, Julieta; Monyer, Hannah; Kuner, Rohini (Scientific reports, 2021)
Maladaptive adult neurogenesis in the mammalian brain has been associated with diverse behaviors including disrupted learning, negative mood disorders and psychiatric conditions. However, its functional role in the generation and maintenance of chronic pathological pain has not yet been elucidated. Using an inducible genetic deletion in vivo mouse model, different behavioural paradigms and home cage monitoring systems, we show that an absence of adult neurogenesis does not impact the development of neuropathic injury-induced peripheral nociceptive hypersensitivity, but rather promotes the recovery of pathological pain as well as improves parameters associated with the state of well-being of the injured mice. These results provide a mechanistic insight into the mechanisms of chronic pain and implicate neurogenic processes as a potential therapeutic target for reducing pain and improving the quality of life for patients.